2022
DOI: 10.3233/jpd-213081
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Procedural Memory in Parkinson’s Disease: A Cross-Sectional, Case-Control Study

Abstract: Background: The analysis of the procedural memory is particularly relevant in neurodegenerative disorders like Parkinson’s disease, due to the central role of the basal ganglia in procedural memory. It has been shown that anterograde procedural memory, the ability to learn a new skill, is impaired in Parkinson’s disease. However, retrograde procedural memory, the long-term retention and execution of skills learned in earlier life stages, has not yet been systematically investigated in Parkinson’s disease. Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Memory impairments have been observed in patients who converted to PD within 2 years but not in the earlier prodromal stages [35]. Based on the results in Set 2, by applying the CUPRO evaluation system [22], we confirmed that the significant difficulties observed in the Cube Copying Task (initial scoring on 1 point [24]) are due to visuoconstructive deficits and not to a deficit of retrograde procedural memory. To our knowledge, the current study is the first to systematically evaluate retrograde procedural memory in P-PD.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Memory impairments have been observed in patients who converted to PD within 2 years but not in the earlier prodromal stages [35]. Based on the results in Set 2, by applying the CUPRO evaluation system [22], we confirmed that the significant difficulties observed in the Cube Copying Task (initial scoring on 1 point [24]) are due to visuoconstructive deficits and not to a deficit of retrograde procedural memory. To our knowledge, the current study is the first to systematically evaluate retrograde procedural memory in P-PD.…”
Section: Discussionsupporting
confidence: 57%
“…To our knowledge, the current study is the first to systematically evaluate retrograde procedural memory in P-PD. Given that, in our previous work on retrograde procedural memory in already diagnosed PD, we did not see any significant correlation between this memory concept and disease duration [ 22 ], we assumed that retrograde procedural memory might be already impaired in the prodromal stages of PD.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Attention and working memory impairment are also common in PD and are characterized by difficulties in sustaining attention, focusing, and filtering out distractions. Patients with attention and working memory impairment may have difficulty remembering and processing new information and may experience frequent lapses in concentration [9] . Visuospatial impairment is characterized by difficulties in processing and interpreting visual information.…”
Section: Introductionmentioning
confidence: 99%